Determinants of Women's Sexual Dissatisfaction: Assessing a Cognitive-Emotional Model. Issue 11 (1st November 2016) - Abdolmanafi, Atefe; Owens, Richard Glynn; Winter, Sam; Jahromi, Reza Ghorban; Peixoto, Maria Manuela; Nobre, Pedro
ABSTRACT: Introduction: Recent studies have demonstrated the role of sexual dysfunctional beliefs, negative automatic thoughts, and emotional responses in relation to sexual functioning. Nevertheless, no studies seem to have evaluated the role of these cognitive-emotional factors in determining sexual dissatisfaction. Aim: To test a cognitive-emotional model of sexual dissatisfaction in women. Methods: In total, 207 women answered questionnaires assessing sexual dissatisfaction and cognitive and emotional variables that might affect sexual dissatisfaction. Main Outcome Measures: Sexual dissatisfaction was measured by the Index of Sexual Satisfaction, sexual beliefs were measured by the Sexual Dysfunctional Beliefs Questionnaire, and thoughts and emotional responses were measured by the Sexual Modes Questionnaire. Results: A path analysis was conducted to assess the conceptual model proposed. Results indicated that dysfunctional sexual beliefs work as predisposing factors by eliciting negative automatic thoughts and emotions, which impair the processing of erotic stimuli and interfere negatively with sexual satisfaction. Conclusion: This finding suggests a role for cognitive and emotional factors in predisposing and maintaining sexual dissatisfaction in women, suggesting relevant implications for intervention.